Social Media Application as a New Paradigm for Business Communication: The Role of COVID-19 Knowledge, Social Distancing, and Preventive Attitudes - Yu, Songbo; Abbas, Jaffar; Draghici, Anca; Negulescu, Oriana Helena; Ain, Noor Ul (Frontiers in Psychology, 2022)
Business firms and the public has encountered massive consequences of the COVID-19 pandemic. This pandemic has become the most significant challenge, and it has influenced all communities. This research study focuses on exploring the relationship between knowledge of COVID-19, social distancing, individuals' attitudes toward social media usage, and practices of using social media amid the COVID-19 crisis. The study examines how attitudes towards social media use mediate the linkage between knowledge of COVID-19, social distancing, and practices for social media use. This survey uses a non-probability convenience sampling approach to collect the samples and recruit willing respondents with their consent for data collection. This study recorded feedback from 348 participants encountering indirect/direct effects of nationwide lockdowns, restrictions on social gatherings, and COVID-19 infections. The findings validate the proposed hypotheses for their direct effects and indicate significant β-values, t-statistics, and the p-values at p<0.001. The results validate a relationship between knowledge of Covid-19 and social distancing practices. Similarly, the results approved a positive link between social distancing and attitude towards social media use amid COVID-19. The findings validate the relation between social distancing and attitudes towards social media use during Covid-19 challenges (β-value = 0.22 and t-statistics= 3.078). The results show the linkage between attitude towards social media use and practices of using social media (β-value = 0.41, and t-statistics= 7.175). Individuals’ attitude towards social media use during COVID-19 mediates the connection between knowledge of COVID-19 and practices of using social media COVID-19. Results validate the first mediation at β-value = 0.21 and t-statistic = 5.327. Similarly, findings approve that attitude toward social media use in the pandemic positively mediates the relation between distancing and practices for social media usage amid the crisis of COVID-19 (β-value = 0.09 and t-statistic = 2.633). The findings indicate how people indulge in social media to pave their business communication needs. The results provide valuable insight for the global business community. This study provides a systematic and holistic research model that helps in exploring the COVID-19 consequences. The generalizability of findings provides valuable directions for future research related to the current pandemic.